Cultural Resistance from the Perspective of Critic Abdullah Rkibi - salhi, nadji; Hima, Abdelhamid (El Omda in Linguistics and Discourse Analysis, 2018)
ABSTRACT : Resistance is voluntary and conscious act. In fact, it is one of the people’s unalienable rights that takes different forms and means. Cultural resistance is one its main forms, it does not stop with the end of colonization. Indeed, it continuous until full independence is achieved. Algerian culture had been under constant falsification and distortion by the French colonizer,which pushed Algerian intellectuals and critics to mobilize themselves to regain what has been lost and restore what has been distorted. AbdallahRekibi was one of those Algerian critics who did their best to dig into our cultural heritage, shedding light on its originality and specificity. Hence, this research is anattempt to find out the ingredients or Algerian culture in the critical discourse in the writings of Rekibi and look how the committed Algerian artist and intellectual has contributed to its preservation.